DESIGN a solar hybrid air conditioning compressor system - Khalaji Assadi, M (EDP Sciences, 2016)
To develop and integrate solar hybrid system into conventional air conditioning system which provides the same cooling load with considerably less electricity demand. Solar evacuated tube and DC compressor are used for compressing the refrigerant in an air conditioning system, thus effectively reducing the air conditioning electricity consumption by up to 45%. For the flow through type selected geometry of the designed evacuated U-tube collector, a three dimensional simulation and analysis of the thermal performance was done, using the solar ray-tracing model provided by the ANSYS-FLUENT software.